H7N7 Avian Influenza Virus Mutation from Low to High Pathogenicity on a Layer Chicken Farm in the UK - Byrne, Alexander M. P. (Viruses, 2021)
Avian influenza virus (AIV) subtypes H5 and H7 are capable of mutating from low to high pathogenicity strains, causing high mortality in poultry with significant economic losses globally. During 2015, two outbreaks of H7N7 low pathogenicity AIV (LPAIV) in Germany, and one each in the United Kingdom (UK) and The Netherlands occurred, as well as single outbreaks of H7N7 high pathogenicity AIV (HPAIV) in Germany and the UK. Both HPAIV outbreaks were linked to precursor H7N7 LPAIV outbreaks on the same or adjacent premises. Herein, we describe the clinical, epidemiological, and virological investigations for the H7N7 UK HPAIV outbreak on a farm with layer chickens in mixed free-range and caged units. H7N7 HPAIV was identified and isolated from clinical samples, as well as H7N7 LPAIV, which could not be isolated. Using serological and molecular evidence, we postulate how the viruses spread throughout the premises, indicating potential points of incursion and possible locations for the mutation event. Serological and mortality data suggested that the LPAIV infection preceded the HPAIV infection and afforded some clinical protection against the HPAIV. These results document the identification of a LPAIV to HPAIV mutation in nature, providing insights into factors that drive its manifestation during outbreaks.